Optimization of silver nanoparticles sizes in ag-cu nanopaste as die-attach materials for high temperature applications - Noordin, Norasiah Mohammad (2017)
Electronic devices used for extreme high temperature (>500oC) for instance in aviation and aerospace applications, continue to be in demand. Ag-Cu nanopaste, which is a mixture of Ag and Cu nanoparticles and organic additives (PVA binder, Ethylene glycol), has been introduced as die attachment technique. By using nanoparticles, the need of external pressure during sintering process is eliminated and the sintering temperature can be reduced by using PVA binder, which has lower burn-off temperature (280oC) as compared to commercial binder V-006A (380oC). In this study, Ag-Cu nanopaste with 0.15 g amount of PVA evaporated at 30 min, displays electrical conductivity value of 3.26 x 105(Ω.cm)-1 at 340oC optimum sintering temperature and 5oC/min heating rate. Further investigation on the combination Ag nanoparticle sizes on electrical, thermal and mechanical properties shows that Set II (150 + 20-50 nm) displays highest electrical and thermal conductivity value, which is 1.15x 105(Ω.cm)-1and 143-181 W/m-K, respectively. However, the shear strength value for Set II is only 0.78 MPa. The mechanical properties of Ag-Cu nanopaste using different binder (commercial binder V-006A) were studied and the bonding attributes recorded is 12.05 MPa at optimum 260oC sintering temperature and 5oC/min heating rate, which is not comparable to the mechanical properties of Ag-Cu nanopaste using PVA binder. In conclusion, Ag nanoparticle sizes (150 + 20-50 nm) offered good electrical and thermal conductivity value as die-attach material for high-temperature applications.